(untitled) (Medicine Today, 2017)
Essential hypertension is a common risk factor for ischemic heart disease. So the Objective of the present study was to find the different angiographic pattern among the symptomatic patients having essential hypertension. A total of 100 symptomatic patients with essential hypertension were evaluated in a one year period by coronary angiography (CAG) in a tertiary care hospital of Chittagong, Bangladesh. Standard protocol and procedure were followed during doing CAG. All data were compiled and were analyzed by SPSS-20. Among 95 patients evaluated male were more 76 (80%) and male to female ratio was 4:1. Most of the patients were involved in service 55(57%). Among all 77(81%) patients were at age group <60 years. Regarding risk factor analysis 39 (41%) patients had DM, 18 (19%) patients had different kinds of dyslipidemia, 66 (69%) patients had hypertension and 25(26.5%) were smoker. Angiographic study revealed 9(9.2%) had involvement of LMCA, 56(58%) had LAD, 29(30%) had LCX, 31(32%) RCA and 18(19%) patients had triple vessel disease. ETT is be a valuable screening tool before doing invasive CAG in our setting. Medicine Today 2017 Vol.29(1): 32-34